(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Use of single donor platelets (SDP) has increased by radical change over past few years. SDP not only increase the quality of product in terms of decreased cellular contamination but also increases the overall yield of platelet collected. However various donor parameter exerts their effect on yield of single donor platelet apheresis.Materials and Methods: The present study included the outcome of 50 SDPA procedures that were conducted on Haemonetics MCS+ intermittent flow cell separator (Haemonetic Corporation). It employs single venous access utilizing closed collection apheresis kits with efficient leuko reduction.Study was undertaken at blood bank M.Y. Hospital associated with M.G.M. Medical College, Indore, and a tertiary care Central Government Teaching Institute from may 2022 to July 2022.Results: Mean platelet count of Donor was 198.6± 27.39. Platelet yield also show statistical significant correlation with HCT (p=o.oo4, r= 0.402) and age (p= 0.042, r= 0.402), No such correlation seen between platelet yield and Heamoglobin (P= 0.0201, r= 0.162).Conclusion: The possibity of obtaining higher platelet yield reduces the frequency of platelet transfusion and number of donor exposures with important consequent clinical and economic advantages.